Ciw: An open-source discrete event simulation library. Issue 1 (2nd January 2019) - Palmer, Geraint I.; Knight, Vincent A.; Harper, Paul R.; Hawa, Asyl L.
Abstract : This paper introduces Ciw, an open-source library for conducting discrete event simulations that has been developed in Python. The strengths of the library are illustrated in terms of best practice and reproducibility for computational research. An analysis of Ciw's performance and comparison to several alternative discrete event simulation frameworks is presented.